2019
DOI: 10.3390/s19173697
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Wired and Wireless Interconnected Body Sensor Networks

Abstract: Current medical facilities usually lead to a very high cost especially for developing countries, rural areas and mass casualty incidents. Therefore, advanced electronic health systems are gaining momentum. In this paper, we first compared our novel off the shelf experimental wired Body Sensor Networks (BSN), that is, Digital First Aid (DigiAID) with the existing commercial product called as Hexoskin. We showed the viability of DigiAID through extensive real measurements during daily activities by both male and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The PDR obtained for n experiments is shown by Eq. (14)[30][31][32][33][34]. Prolong the lifetime of the network is the main goal of WSNs.…”
mentioning
confidence: 99%
“…The PDR obtained for n experiments is shown by Eq. (14)[30][31][32][33][34]. Prolong the lifetime of the network is the main goal of WSNs.…”
mentioning
confidence: 99%
“…The results obtained from the developed sensor are compared with the results from the reference nasal e-Health sensor (e-Health AirFlow sensor, Cooking Hacks) which was validated by several studies in the literature [31]- [34]. The e-Health sensor detects the variation in temperature of the nasal airflow.…”
Section: Sensorsmentioning
confidence: 97%
“…This is not strange considering that Hexoskin collects data using a one-channel ECG sensor. Talpur et al (2019) [65] noted that the HR values collected using the wired DigiAID were acceptable, but not satisfactory. Studying the sleep activity data, the RR data were fluctuating for both systems, but within the reference RR range for all participants with the wired DigiAID.…”
Section: Additional Use Of Wearable Sensors In Contexts Related To Ncdsmentioning
confidence: 99%
“…The authors found the sensors reliable and stable for EEG signal acquisition. Talpur et al (2019) [65] presented a wearable, but wired off-the-shelf sensor network, DigiAID, that included a pulse oximeter for measuring HR, an airflow sensor for measuring RR and a position sensor. The viability of using the wired DigiAID for measuring HR and RR was determined by comparing the sensor data collected with data collected using the Hexoskin garment.…”
Section: Additional Use Of Wearable Sensors In Contexts Related To Ncdsmentioning
confidence: 99%
See 1 more Smart Citation